PENAMBAHAN SARI KUNYIT (Curcuma domestic Val) TERHADAP PERTAMBAHAN BERAT BADAN DAN KONSUMSI PAKAN AYAM PETELUR JANTAN - Andri Dwi Effendi; Nita Opi A.K; Adi Andaka (Universitas Islam Balitar, 2017)
It has been done a research about Curcuma Domestic Val to egg-type cockerels of hen. This research is knowing about of effect curcuma domestic val to increas weight a hen. Its used a egg-type cockerels strain Isa Brown from PT. Charoen Pokphand Indonesia more than 60 hens that old is 30 days until 58 days is ready, and curcuma domestic val that fresh juice. After 30 days old, its been done to 12 team of boxes. Every box has been 5 hens, then doing it until 1-12 agains, to 12 team of boxes assigned into 4 treatments with 3 replication. This research used experiment that completely randomized design with 4 kinds of method. According this research, can be summary that to added Curcuma Domestica Val with water can ’t real effect to in crease weight (P>0.05), with higher to P0,P1,P2,P3. That mean is 89,6, 895, 873,3, 864,3, its must to do research more than extra about to added Curcuma Domestic Val with volume more than 50 ml/1000 ml water to added weight of egg-type cockerels, so its can to know size how much ml Curcuma Domestic Val that can be responses.Keywords : Egg-type cockerels:, Body Weight, Curcuma Domestic Val